The Relationship of Brand Image and Brand Trust to Patient Loyalty at Intan Medika Lamongan Hospital - Rina Anggun Widyastuti; Junita Anggraini; Amirul Amalia; Atiul Impartina; Alifin; M Ganda Saputra; Nihayatul Munaa (Jurnal Surya, 2024)
Introduction: Brand image is a consumer's response to a brand based on the good and bad of the brand that consumers remember. Patient Loyalty is not only built through brand image but also brand trust, Trust arises as a result of the reliability and integrity of partners shown through the attitude of consistency, competence, integrity and benevolence. The purpose of this study is to determine the relationship between brand image and brand trust to patient loyalty at Intan Medika Lamongan Hospital. Methods: This study is quantitative analysis with a cross sectional design, using a nonprobability sampling technique with an incidental sampling method obtained from 100 respondents. The independent variable is brand image and the dependent brand trust is patient loyalty. The three variables in this study used a closed questionnaire as the instrument. Results: This study obtained the results of some (57%) patients rated brand image Good and (43%) patients rated Very Good, some (82%) patients rated brand trust Good (7%) patients rated Very Good while (11%) patients rated Poor, and some (56%) patients had High loyalty (6%) patients had Very High loyalty (38%) patients had Low loyalty. To test the correlation coefficient, this study used the SPSS 16.0 For Windows program using the Searman Rank test, in testing the relationship between brand image and loyalty, a value of rs=0.097 and a value of p=0.333 were obtained, meaning that there was no relationship between brand image and loyalty, while in testing brand trust with loyalty, a value of rs=0.419 and a value of p=0.000 were obtained, meaning that there was a relationship between brand trust and patient loyalty. Conclusion: It is hoped that the results of this study can increase Brand Trust in order to increase patient loyalty at Intan Medika Hospital. Keywords: Health worker, Knowledge, Occupational Health and Safety (K3)